Caffeine in Tris Egg Yolk Citrate Extender Improves the Antioxidant Potential of Cryopreserved Surti Buck Semen - Bhut, Darshita Vijaybhai; Khasatiya, Chandubhai Talshibhai; Singh, Virendra Kumar (The Indian Journal of Animal Reproduction, 2024)
The study was conducted to evaluate the antioxidant action of caffeine at various concentrations in TEYC extenders. In the present study, a total 64 ejaculates (16/buck) were collected from all four Surti bucks (age>12 months) i.e. two collections/week for 8 weeks. Ejaculates at each collection were pooled and divided into four groups viz. C1 (Control), C2, C3 and C4 having caffeine concentrations @ 0, 1, 3 and 5mM in TEYC extender, respectively with 100x106 sperm/ • Oxidative stress marker for lipid peroxidation (Malondialdehyde, MDA) and antioxidant (Glutathione, GSH) were determined at initial, pre-freeze and post-thaw; whereas, motility degeneration rate (MDR) of sperms was evaluated at pre-freeze and post-thaw. A decrease in GSH and an increase in MDA levels with elapse of time were found to be significant (p<0.01) between different phases. The MDA levels were observed to be significantly (p<0.01) different between groups that were highest in C1 and lowest in C4 in contrast to GSH levels that were highest in C4 and lowest in C1 groups. MDR was significantly (p<0.01) higher at post-thaw than pre-freeze in all the groups. Moreover, MDR was significantly (p<0.01) lower in C2 group as compared with other groups at both the pre-freeze and post-thaw stage. It was therefore concluded that for cryopreservation of Surti buck semen, supplementation of caffeine in TEYC extender has dose-dependent increase in antioxidant defense and decrease in oxidative stress as indicated by higher GSH and lower lipid peroxidation, respectively but 1mM caffeine concentration in TEYC is optimum and better owing to the lowest MDR.